Influence of culture media on in-vitro fertilization of goat oocytes - KHARCHE, S D; YADAV, E N; GOEL, A K; JINDAL, S K; SINHA, N K (The Indian Journal of Animal Sciences, 2011)
The present investigation was undertaken to evaluate the influence of culture media on in-vitro fertilization rate of goat oocytes. Ovaries (250) were collected from local abattoir and transported within 4 h to the laboratory in warm saline (37Â°C) containing 100 IU penicillin-G and 100 g streptomycin sulphate/ml. Cumulus oocyte cOlllplexes (630) retrieved by follicle puncture technique were selected for in-vitro maturation of which 489 were subsequently utilized for in-vitro fertilization and culture. Oocyte were ulatured in TCM-199 medium supplemented with 20% estrus goat serum at 38.5Â°C and 5% CO2 under humidified air for 27 h. After 27 h of in vitro maturation, oocytes were denuded, washed and randomly divided in to 3 groups. Group 1 (n=167), group 2 (n=137) and group 3 (n=185) in-vitro matured oocytes were co-incubated spermatozoa in a 50 III drop of mTALP, BO and mSOF media, respectively. Oocytes-spemt after 18 h of co-incubation were washed in culture medium for 15-20 times and cultured in 50 /-11 drop of culture medium. Cleavage of in-vitro fertilized oocytes was observed at 48 h post insemination under inverted phase contrast Inicroscope. The average oocyte recovery and maturation rate were 2.52 and 77.61 %, respectively. The cleavage rate in group 1 (59.72%) was significantly higher (P<0.05) than that of group 2 (32.84%) and group 3 (36.21 %) in-vitro matured oocytes. From the present study it is concluded that the utilization of mTALP as fertilization medium have significantly (P<0.05) increased the cleavage rate of in-vitro matured goat oocytes as compared to BO and mSOF medium. Â